2020
DOI: 10.1002/cite.201900130
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung von Polymerablagerungen während der Synthese in einem Wärmeübertrager

Abstract: Zur Untersuchung der unerwünschten Belagbildung von Polymeren auf wärmeübertragenden Oberflächen (Polymerisationsfouling) wird das Ablagerungsverhalten eines Vinylacetat/Vinylester-Copolymers während der Emulsionspolymerisation untersucht. Hierbei sollen grundlegende Unterschiede zum Ablagerungsverhalten eines bereits reagierten Vinylacetat/Ethylen-Copolymers identifiziert werden. Für einen qualitativen Vergleich wird die Ablagerungstopographie mithilfe eines Digitalmikroskops bestimmt. Für die quantitative Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Fouling processes during emulsion polymerisation of vinyl acetate are investigated in literature as well. There are different publications discussing this topic [17,[32][33][34]. Carvalho et al [17] investigated the continuous emulsion copolymerisation of vinyl acetate and n-butyl acrylate in a tubular reactor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fouling processes during emulsion polymerisation of vinyl acetate are investigated in literature as well. There are different publications discussing this topic [17,[32][33][34]. Carvalho et al [17] investigated the continuous emulsion copolymerisation of vinyl acetate and n-butyl acrylate in a tubular reactor.…”
Section: Introductionmentioning
confidence: 99%
“…In these publications the influences of temperature and surface modifications on fouling masses are discussed and it could be shown that higher temperatures lead to higher fouling masses. For surface modifications a general trend could not be observed as it is highly dependent on the other process parameters [32][33][34]. Hohlen et al [33] investigated the differences between fouling of reactive emulsion polymerisation systems compared to the fouling of non-reactive polymer dispersions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For surface modifications no general trend could be observed as it is highly dependent on the other process parameters 37 39 . Hohlen et al 38 compared fouling of reactive emulsion polymerisation systems with fouling of non-reactive polymer dispersions. Reactive polymerisation systems cause much higher fouling masses than non-reactive so polymerisation fouling is the major part.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive polymerisation systems cause much higher fouling masses than non-reactive so polymerisation fouling is the major part. Moreover, the morphology of the fouling is given by the pathway of formation so the dominant fouling process can be concluded optically from the fouling morphology 38 .…”
Section: Introductionmentioning
confidence: 99%